Analiza ostankov plena iz gnezda škrjančarja Falco subbuteo - Kozinc, Boris (Acrocephalus, 1999)
In the period from July 15th to August 10th 1995, some remains of prey and pellets were taken on six occasions by the author of this article from the nest of Hobby Falco subbuteo in the vicinity of Lesce in the Gorenjska region.The nest containing three chinks was situated in the Scotch Pine Pinus sylvestris woodland along the Sava river. The analysed sample contained remains of captured birds, rodents and bats as well as pellets of the young aged from ten days pnwards. The following animals were determined: Blackbird Turdus merula, Song Thrush Turdus philomelos, vole Arvicola terrestris, noctule Nyctalus noctula, and little bat Pipistrellus pipistrellus. Apart fromthe remains of feathers and hairs, yellow coverts belonging to either Greenfinch or the European Goldfinch, as well as chitinous remains of beetles and of a snail shell were found in the pellets.
Keywords: bird; Birds; ptice; ornitologija; Ecosystem; gnezdenje; Animal nutrition